Capabilities of the Chromatek-DHA Software for Determining the Quality of Automobile Gasoline - O. V. Samoilova (Теория и практика судебной экспертизы)
The article addresses factors able to influence the results of determining the performance characteristics of gasoline using calculation methods. The author presents the results of a study of three brands of automobile gasoline conducted by means of gas-liquid chromatography with Chromatek-DHA software. The calculated operational characteristics of gasoline have been compared with the results of their analysis by standardized methods. The article demonstrates the possibility of using data on the group hydrocarbon composition in solving expert identification tasks regarding automobile gasoline that has not been exposed to external factors.